Embryological incubation temperature modulates behaviour in larval white sturgeon (Acispencer transmontanus) - Hamilton, Trevor; Cheung, Katherine; Hudson, James; Szaszkiewicz, Joshua; Ingraham, Erica; Krook, Jeffrey; Johnson, Andréa; Franczak, Brian; McAdam, Steve; Brauner, Colin J. (My University, 2025)
White sturgeon inhabit large rivers and estuaries along the Pacific coast of North America and play important ecological and cultural roles. As with other poikilotherms, the expected rise in global temperatures will create physiological challenges for sturgeon, including direct effects on physiological rates, and may also cause changes in behaviour that impact survival. In this study, we investigated ‘carryover effects’ in white sturgeon (Acipenser transmontanus) by incubating fish at one of three embryological temperatures (12 °C, 15 °C, or 18 °C) from fertilization to hatch, and then holding them at 15 °C for the following 30 days post-hatch (dph). We investigated the effect of these incubation temperatures on subsequent behaviours, including locomotion and anxiety-like behaviour, at 18, 24 and 30 dph. The open field test was used to quantify distance moved by the fish and time spent near the outer wall of the arena (to quantify thigmotaxis, an indicator of anxiety-like behaviour) and recorded with motion-tracking software. This test was also used to compare behaviour during the day versus night (at 21 dph) and hourly at night (at 28 dph). Additionally, a light/dark test commonly used in rodents and other fish species was performed for the first time on larval sturgeon at 24 dph. We found a significant family effect; the impact of embryo rearing temperature on locomotion and thigmotaxis varied depending on the family lineage of the fish. Furthermore, we provide evidence that larval sturgeon exhibit greater locomotion at 24 and 30 dph compared to 18 dph, and have a preference for the light zone of the light/dark test. Our findings identify a more nuanced effect of incubation temperature on later life stages that varies with family lineage and underscores the need to consider such variation in research and conservation programs.
Keywords: white sturgeon; temperature; climate change; locomotion; anxiety